Spectrum of non-fermenting gram negative bacilli isolated from patients with blood stream infections in a tertiary care hospital in North India - Nazir, Asifa; Peerzada, Bushra Yousuf; Sana, Ifshana (International Journal of Research in Medical Sciences, 2019)
Background: Non-fermenting Gram-negative bacilli (NFGNB) are emerging as important causes of blood stream infections (BSI) and they are a major cause of morbidity and mortality worldwide. High intrinsic resistance of NFGNB to antimicrobial compounds makes the treatment of BSIs caused by them difficult and expensive. The aim of this study was to assess frequency and antibiotic susceptibility pattern of non-fermenting gram-negative rods isolated from blood culture of patients. Methods: A total of 3016 blood samples were received in the Department of Microbiology during the study period. All samples were processed according to standard microbiological procedures. Blood culture was done by automated blood culture system, (BacT/Alert) and identification and antibiotic susceptibility of non-fermenting gram negative bacilli was done by VITEK2 Compact System. Results: A total of 120 NFGNB were identified out of which the most common non-fermenters isolated were Acinetobacter sp. (95) followed by Pseudomonas aeruginosa (11), Burkholderia cepacia (09) Sternotrophomonas maltophilia (03) and Sphingomonas sp. (02). Most of the non -fermenters were multi drug resistant showing a high level of antibiotic resistance to most of the first- and second-line drugs. The most effective drugs were colistin and tigecycline. Conclusions: This study underlines the need to identify NFGNB in tertiary care hospitals and to monitor their susceptibility pattern to guide the clinician for better care and management of patients. Improved antibiotic stewardship and strict infection control measures especially hand washing need to be implemented to prevent emergence and spread of multidrug resistant NFGNB in health care settings.